Enhanced grain quality of malt barley (Hordeum distichon L.) in response to mixed use of organic compost and mineral nitrogen rates - Arega Wole; Amsalu Nebiyu; Getachew Agegnehu; Yenus Ousman (PLoS ONE, 2026)
Declining soil fertility status and poor agronomic management practices are major factors of declining quality for malt barley in the Ethiopian highland area, particularly in the study area. To address these major challenges, a two-year (2022−2023) field experiment was conducted in experimental fields in the Welmera district to evaluate the effects of mixed-use mineral N fertilization and compost rates on malt barley quality parameters. A randomized complete block design with factorial arrangements of five N rates (0, 23, 46, 69, and 92 kg ha -1 ) and four compost rates (0, 2.5, 5, and 7.5 t ha -1 ) was tested in three replications. According to the results, both compost and mineral nitrogen fertilizer were significantly influenced thousand-seed weight, protein content, malt extract, beta-glucan content, malt friability and germination energy of malt barley grain, with seasonal variations. Increased mineral N levels enhanced seed weight and grain protein content but reduced malt extract yield and malt friability, while compost improved grain protein content and malt beta-glucan. These influences were improved by organic compost and mineral fertilization, which enhanced multiple quality parameters. The results clearly demonstrated that application of 69 kg N ha -1 and 5 t ha -1 of compost rate in moderation, which optimized the malt quality parameters, met industry standards without increasing protein concentration or diminishing malt extract yield of malt barley grain. These mixed management approaches not only enhance the quality of malt barley grain for the beer industry but also help soil fertility restoration and guarantee long-term production sustainability for smallholder farmers in the Ethiopian highlands. For robust and wide applicability, subsequent multiple-seasons and multiple-locations studies with additional quality assessments are recommended.